2020
DOI: 10.1002/jhet.3921
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis, molecular docking, and spectral studies of new class of carbazolyl polyhydroquinoline derivatives as promising antibacterial agents with noncytotoxicity towards human mononuclear cells from peripheral blood

Abstract: In the present study, we report the design and eco‐benign synthesis of new class of carbazolyl‐1,4‐dihydropyridine (1,4‐CDHP) and carbazolyl‐1,8‐dioxodecahydroacridine (CAD) derivatives via a three‐component coupling reaction of substituted carbazole aldehydes, ethyl acetoacetate/dimedone, and ammonium acetate under solvent‐free conditions at 112°C to 115°C. We also report an efficient one‐pot synthesis of new class of carbazolyl polyhydroquinoline (CPQ) derivatives via a four‐component coupling reaction of su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 31 publications
(33 reference statements)
1
8
0
Order By: Relevance
“…For this purpose, 4-pyridine-carboxaldehyde (2b), 9-ethyl-9H-carbazole-2-carbaldehyde (2c), 2,3-dimethyl-5-oxo-1-phenyl-3-pyrazoline-4carboxaldehyde (2d), 5-methylfuran-2-carboxaldehyde (2e) and ferrocenecarboxaldehyde (2f) were treated with the mentioned conditions above. The reaction of 2b and 2c with dimedon was reported by literature [30][31][32][33] afforded 3b and 3c 83 % and 87 % respectively. We synthesized 3b and biologically active 3c compounds with higher yields in milder conditions and shorter times.…”
Section: Resultssupporting
confidence: 54%
“…For this purpose, 4-pyridine-carboxaldehyde (2b), 9-ethyl-9H-carbazole-2-carbaldehyde (2c), 2,3-dimethyl-5-oxo-1-phenyl-3-pyrazoline-4carboxaldehyde (2d), 5-methylfuran-2-carboxaldehyde (2e) and ferrocenecarboxaldehyde (2f) were treated with the mentioned conditions above. The reaction of 2b and 2c with dimedon was reported by literature [30][31][32][33] afforded 3b and 3c 83 % and 87 % respectively. We synthesized 3b and biologically active 3c compounds with higher yields in milder conditions and shorter times.…”
Section: Resultssupporting
confidence: 54%
“…[37] Venkatapathy et al synthesized number of carbazolyl polyhydroquinoline compounds (b) and screened them against pathogenic strains of gram positive and gram negative bacteria which have superior activity against six strains of gram positive and gram negative bacteria such as Escherichia coli, Shigella dysenteriae, Pseudomonas aeruginosa, Streptococcus pneumonia, Salmonella typhi and Staphylococcus aureus. [38] In recent years, Nosrati et al synthesized number of polyhydroquinoline derivatives (c) and investigated their antimicrobial activities which exhibit good activity against gram-positive bacteria S. aures. [39] Similarly, Zainab et al reported various compounds based on PHQ nucleus, which exhibit significant antibacterial activity against Escherichia coli (gram-negative bacterium)…”
Section: Introductionmentioning
confidence: 99%
“…et al . synthesized number of carbazolyl polyhydroquinoline compounds ( b ) and screened them against pathogenic strains of gram positive and gram negative bacteria which have superior activity against six strains of gram positive and gram negative bacteria such as Escherichia coli , Shigella dysenteriae , Pseudomonas aeruginosa , Streptococcus pneumonia , Salmonella typhi and Staphylococcus aureus [38] . In recent years, Nosrati et al .…”
Section: Introductionmentioning
confidence: 99%
“…Exploring non-toxic, effective, and safe chemotherapeutical gents is still a very important concern due to the growth of multi-resistant bacterial strains [ 25 , 26 ]. Infectious diseases continue to attack human beings with opportunistic infectious disorders, and infection with drug-resistant microorganisms [ 27 , 28 ]. During recent years, the treatment of bacterial infections has been challenging in patients with weak immune systems or with other associated diseases [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%